THE EFFECT OF MUDHARABAH, MUSYARAKAH AND MURABAHAH FINANCING ON NET PROFIT IN PT. BANK MUAMALAT INDONESIA, Tbk - ayu rumi; arbanur rasyid; ali hardana; sulaiman efendi (Journal Of Sharia Banking, 2020)
This research is a quantitative research using multiple linear regression data analysis with data collection techniques used are documentation and literature study. The data was processed using statistical calculations with the SPSS 23.0 computer program, with a total sample of 53 samples whose data was obtained through the website www.ojk.go.id. The results showed that partially mudharabah financing had an effect on net income because the value of tcount ttable (2,011 2,009), musyarakah financing had an effect on net income because the value of -tcount -ttable (-1,925 -2,009), and murabahah financing had an effect on profit. net because the value of tcount ttable (2,366 2,009). Simultaneously, mudharabah, musyarakah and murabahah financing affect net income because the value of Fcount Ftable (5.689 2.79). The effect of mudharabah, musyarakah and murabahah financing on net income is 25.8%, while the remaining 74.2% is influenced by other factors not included in this study.